The Role of Plant Growth Promoting Rhizobacteria (PGPR) in Sustainable Agriculture - Huda Asra, Rahmatul; Advinda, Linda; Anhar, Azwir; Irdawati (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
The majority of farmers currently use chemical fertilizers and pesticides in farming. However, continuous use of these materials can cause negative impacts such as environmental pollution, health risks, nutrient cycle imbalances, and reduced crop yields. To overcome this problem, research has been conducted that focuses on the use of microorganisms found in the soil layer surrounding plant roots, called the rhizosphere. These microorganisms such as bacteria, fungi and protozoa form a group known as Plant Growth Promoting Rhizobacteria (PGPR). PGPR can increase plant growth through various mechanisms such as nitrogen fixation, phosphorus dissolution, production of cyanide acid compounds (HCN), and Indole Acetic Acid (IAA) compounds. This research aims to collect and analyze articles related to the role of PGPR in sustainable agriculture. The method used is a literature review by collecting sources from Google Scholar and other internet databases. The results of the articles collected were on topics related to PGPR, including mechanisms of nitrogen fixation and phosphorus solubilization, as well as their role in producing IAA and siderophores. Apart from that, the research also discusses the role of PGPR as a biocontrol agent that can control plant pathogens, and the antagonistic activity of PGPR against pathogens.